Factors influencing hand hygiene among dental personnel at the outpatient clinic of a Tertiary Hospital in Indonesia - Sylvia Fatridha Situngkir (Wolters Kluwer Medknow Publications, 2019)
Background: Nosocomial infections are acquired during hospitalization, and they are strongly influenced by the healthcare workers' hand hygiene. Many factors can affect hand sanitation compliance, including healthcare worker's perception, profession, high workload, lack of time, access to hand washing materials, presence of skin irritation, team of healthcare workers, and knowledge regarding the importance of hand sanitation. Objective: The aim of this study was to determine the influence of individual factors (knowledge, perception, and profession), the availability of hand sanitation facilities, and the hand hygiene workload on the hand sanitation compliance among dental personnel. Method: This quantitative observational study involved 36 dentists and 14 dental hygienists at the outpatient dental clinic of the Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia, from July 2013 to January 2014. The data were obtained via observation and questionnaires, and it was analyzed using univariate and bivariate analyses (Chi-square test) and a multivariate analysis with a logistic regression. Result: There were no correlations between the knowledge (P = 0.086) or profession (P = 0.181) and the hand sanitation compliance. However, significant correlations were found between the hand sanitation compliance and the individual perception toward hand sanitation (P = 0.000), availability of hand sanitation facilities (P = 0.000), and hand hygiene workload (P = 0.029). Conclusion: The factors that influenced the dental personnel's compliance to the hand sanitation procedures at the outpatient dental clinic were the availability of the hand sanitation facilities and the individual perceptions of the dental personnel. However, further research is needed to determine the level of hand sanitation compliance when using hand rubs and liquid soap.